Brilliant interview : - Jay, Ros (Pearson/Prentice Hall Business, 2005)
What do interviewers really want from a candidate? How do they decide whether to hire you or someone else? What can you do to make it you? Who better to advise interviewees than interviewers? This book tells you what they want and teaches you how to deliver. Like "Brilliant CV," this book is highly practical and interactive. Find out what works in the real world and put it into practise through text features such as tips from the experts, shining examples, horror stories, questions and quizzes to get you thinking. It is clear enough for new interviewees, and has enough detail and thought-provoking ideas to revamp the technique of those more practised at job interviews. Read this book and arm yourself with the advantage of knowing what interviewers are looking for and how supply it. Learn to show yourself in the best possible light and maximise your chances of getting the job.